How Can the Church Reclaim Backsliders? Analysis of Church Education to Reclaim Backsliders - Htay, Kyaw Myint; Salurante, Tony (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Backsliding is a problem occurring among Christians in Myanmar. The author focuses this research on seeking several solutions to the issue of backsliding among Christians in Myanmar by comparing it with the Reformed worldview. The analytical focus is on the educational aspect in the church to address backsliding based on the Reformed worldview. This research was conducted in several stages, including problem identification and its causes, proposing problem-solving ideas. The researcher conducted interviews among Christians and elaborated with various other literary sources. The research findings reveal that the church needs to teach sound doctrines that can help its members grow in their faith and withstand difficult times. Political and religious issues are inseparable, but the fundamental problem is the need for contextual churches. The church needs to love and care for its flock. Additionally, the research finds that contextual churches require influence in every public area. Church leaders in urban areas need to be more educated and aware of the views and sensitivities of various ethnic, class, race, and religious groups. The church, as the body of Christ, should be able to communicate the Word of God honestly and accurately to its members and ensure that they are engaged in Bible classes or groups where they can learn and enjoy fellowship with fellow believers to strengthen their faith.